(untitled) (Journal of the College of Basic Education, 2025)
Education is one of the basics of life. Without it, nations do not advance, sciences and scientific studies do not advance, and discoveries that contribute to the advancement of human life do not occur. The importance of this research lies in shedding light on the transformations that the educational system has witnessed as a result of the increasing use of e-learning technologies, which has affected teaching strategies and evaluation methods. The method of education that occurs directly between the instructor and the pupils is known as traditional education. Speaking in front of pupils is one of the more conventional teaching techniques. Self-learning via computers or mobile devices is known as e-learning. The most notable of e-learning’s numerous advantages is that it saves time and money because it is inexpensive and allows students to access it from any location because they do not have to leave their homes or places of employment to attend classes. It offers extremely well-designed information, and students’ overall academic performance may be raised by balancing and integrating the benefits of the two systems.